Respostas

2014-03-26T18:51:44-03:00
A )  3x + 1 = 10
      3x = 10 - 1
      3x = 9 
        x = 9 / 3
        x = 3

b ) 3x + 1 = 13
     3x = 13 - 1
     3x = 12
       x = 12 / 3
       x = 4 

c ) 3x + 1 = 16
     3x = 16 - 1
     3x = 15
       x = 15 / 3
       x = 5

d ) 3x + 1 = 19
     3x = 19 - 1
     3x = 18
       x = 18 / 3
       x = 6

e ) 3x + 1 = 22
     3x = 22 - 1
     3x = 21
       x = 21 / 3
       x = 7

f ) 3x + 1 = 13
    3x = 13 - 1
    3x = 12
      x = 12 / 3
      x = 4 

g ) 3x + 1 = 28
     3x = 28 - 1
     3x = 27
       x = 27 / 3
       x = 9 
2 5 2